AN ANALYSIS OF ENGLISH TEACHERS’ STRATEGIES ONE -LEARNING CLASSES DURING COVID-19 AT SMK NEGERI 1 PEMATANGSIANTAR - Rohdearni Sipayung; Lince Pardede (Program Studi Pendidikan Bahasa Inggris FKIP, 2021)
The purpose of the study is to analyze the strategies of the English teacher on E-learning classes during covid-19 at SMK Negeri 1 Pematangsiantar. This type of research was field research with qualitative approach. This study aimed at answering the following research questions: (1) what are the strategies on English e-learning classes during the COVID-19 pandemic at SMK Negeri 1 Pematangsiantar? Data collection techniques in this study are observation, interview, and documentation. The results of the study show that (1) The teachers use different strategies because the expected skill output are different, for writing skills the teacher uses 3 strategies namely planning, drafting, and editing. As for listening skills, the teacher applies several strategies such as listening to songs, writing song lyrics, matching lyrics, and finally sing a songs. For reading the researcher find 2 strategies, like that reading of textbook, and observed, and make a sentence. For the, speaking the researcher find the strategies such as using video on you tube, conversation, and make poetry. But all of them use the video-based learning model and also virtual education through WhatsApp. (2) Strategies in teaching through e-learning classes during the COVID-19 pandemic greatly assisted teachers in the teaching and learning process to achieve learning goals